Sobre rigidez de hipersuperfícies completas - Aquino, Cícero Pedro de (2011)
The purpose of this thesis is to obtain characterization theorems of complete spacelike hypersurfaces isometrically immersed in a semi-Riemannian ambient space under some restrictions on the Gauss mapping or about the r-mean curvatures of these objects. We start our work by providing necessary conditions to ensure the umbilicity of immersed hypersurfaces in the hyperbolic space Hn+1 with prescribed Gauss mapping. Next, we obtain some uniqueness results of complete hypersurfaces with bounded higher order mean curvatures in a space ER x et Mn where we suppose an appropriate condition on the normal angle of the hypersurface. In the last part of this work, we obtain Bernstein-type results concerning to complete vertical graphs with constant mean curvature immersed in a Riemannian warped product I x f Mn, where we suppose a well know convergence condition on the sectional curvature of the fibre Mn.